6th AeU Convocation 2016: Harnessing Technology & Transforming Lives - Asia e University, AeU (AeU, 2016)
The sixth Convocation was held on Saturday, 15th October 2016 at the Dewan Merdeka, Putra World Trade Cenre, Kuala Lumpur. Conferment of degrees took place over 3 sessions.